The strange careers of the Jim Crow North : segregation and struggle outside of the South - Purnell, Brian, 1978-; Theoharis, Jeanne; Woodard, Komozi (New York University Press, 2019)
"The Strange Careers of the Jim Crow North explores the topics of racism and segregation"--